Sulfonium-based liposome-encapsulated antibiotics deliver a synergistic antibacterial activity. Issue 6 (24th May 2021) - Patel, Anjali; Dey, Subhasis; Shokeen, Kamal; Karpiński, Tomasz M.; Sivaprakasam, Senthilkumar; Kumar, Sachin; Manna, Debasis
Abstract : The devastating antibacterial infections, coupled with their antibiotic resistance abilities, emphasize the need for effective antibacterial therapeutics. Abstract : The devastating antibacterial infections, coupled with their antibiotic resistance abilities, emphasize the need for effective antibacterial therapeutics. In this prospect, liposomal delivery systems have been employed in improving the efficacy of the antibacterial agents. The liposome-based antibiotics enhance the therapeutic potential of the new or existing antibiotics and reduce their adverse effects. The current study describes the development of sulfonium-based antibacterial lipids that demonstrate the delivery of existing antibiotics. The presence of cationic sulfonium moieties and inherent membrane targeting abilities of the lipids could help reduce the antibiotic resistance abilities of the bacteria and deliver the antibiotics to remove the infectious pathogens electively. The transmission electron microscopic images and dynamic light scattering analyses revealed the liposome formation abilities of the sulfonium-based amphiphilic compounds in the aqueous medium. The effectiveness of the compounds was tested against the Gram-negative and Gram-positive bacterial strains. The viability of the bacterial cells was remarkably reduced in the presence of the compounds. The sulfonium-based compounds with pyridinium moiety and long hydrocarbon chains showed the most potent antibacterial activities among the tested compounds. Mechanistic studies revealed the membrane-targeted bactericidal activities of the compounds. The potent compound also showed tetracycline and amoxicillin encapsulation and sustained release profiles in the physiologically relevant medium. The tetracycline and amoxicillin-encapsulated lipid showed much higher antibacterial activities than the free antibiotics at similar concentrations, emphasizing the usefulness of the synergistic effect of sulfonium-based lipid and the antibiotics, signifying that the sulfonium lipid penetrated the bacterial membrane and increased the cellular uptake of the antibiotics. The potent lipid also showed therapeutic potential, as it is less toxic to mammalian cells (like HeLa and HaCaT cells) at concentrations higher than their minimum inhibitory concentration values against S. aureus, E. coli, and MRSA. Hence, the sulfonium-based lipid exemplifies a promising framework for assimilating various warheads, and provides a potent antibacterial material.